Preparation method of transparent conductive base layer and electrochromic assembly
By limiting the preparation methods and parameters of the transparent conductivity grassroots, control the deposition and baking temperature, solve the problem of rising square resistance of the transparent conductive layer, and achieve lower square resistance and better transmission rate, improve the electrical discoloration component component Performance.
Patent Information
- Application Number
- CN202411503398.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-01-24
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the prior art, the resistance of the transparent conductive layer will increase significantly after the subsequent lamination process, resulting in the impedance of the conductive layer at the lower part of the electrochromic film layer becoming larger, and an effective color discoloration function cannot be achieved.
By limiting the preparation methods and parameters of the transparent conductivity, including physical gas deposition and vacuum baking treatment, controlling deposition temperature ≤120 ℃ and baking temperature of 200 ℃ ~ 400 ℃, to ensure that the square resistance is not elevated or even decreased.
Without changing the thickness of the transparent conductive film, it is ensured that the sheet resistance will not increase or even drop to a lower level, thereby improving the transmittance and roughness of the product and enhancing the performance of the electrochromic component.
Smart Images

Figure BDA0005103166460000081 
Figure BDA0005103166460000091
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electrochromic products and relates to a preparation method of a transparent conductive base layer and an electrochromic component. Background Art
[0002] As the size of electrochromic products becomes larger and the color change response time is required to be shorter, the requirements for the stability of the sheet resistance of the underlying transparent conductive film are getting higher and higher. It is necessary to ensure that the sheet resistance is stable and the sheet resistance is as low as possible based on a certain film thickness. Therefore, a stable and low sheet resistance of the underlying conductive layer is the key to meeting the above high requirements of electrochromic products.
[0003] The prior art solution discloses a method for manufacturing a transparent conductive film with a crystalline structure, the method comprising the following steps: after the substrate enters a vacuum chamber, the substrate temperature is maintained at room temperature or not more than 50°C; a layer of transparent conductive film is deposited on a surface of the substrate by magnetron sputtering; another transparent conductive film of different composition is deposited on the deposited transparent conductive film by magnetron sputtering; and the substrate coated with the transparent conductive film is subjected to a heating treatment at a temperature below 160°C.
[0004] The prior art solution discloses a substrate with p-type amorphous silicon and a transparent conductive oxide film and a preparation method thereof, the method comprising preparing a substrate with a transparent conductive oxide film; forming a texture on the surface of the substrate with the transparent conductive oxide film to obtain a substrate with a textured surface structure and a transparent conductive oxide film; and forming an amorphous silicon p-type layer on the substrate with the transparent conductive oxide film with a textured surface structure using a physical vapor deposition method to obtain a substrate with p-type amorphous silicon and a transparent conductive oxide film.
[0005] The prior art solution discloses a novel composite transparent conductive oxide film, which is particularly suitable for thin-film solar cell technology, and specifically includes at least one layer of intrinsic zinc oxide film or doped zinc oxide film with a velvet structure prepared by low-pressure chemical vapor deposition or metal organic chemical vapor deposition method and at least one layer of doped transparent conductive oxide film, forming a composite transparent conductive oxide film.
[0006] However, the existing technology still has problems such as the square resistance will increase significantly when the bottom transparent conductive layer undergoes the subsequent lamination process; the impedance of the conductive layer below the electrochromic film layer becomes larger and cannot achieve effective color change function; currently, fluorine-doped tin oxide film materials are used to replace transparent conductive film materials, or the thickness of the transparent conductive film is increased by several times to weaken the influence of unstable thermal stability of square resistance, but the existing fluorine-doped tin oxide film material has a large surface roughness that seriously affects the product life; some manufacturers have added a polishing and grinding process for fluorine-doped tin oxide film materials, but it greatly increases the cost; the increase in the thickness of the transparent conductive film also increases the production cost, and also reduces the product's transmittance performance. Therefore, it is urgent to design and develop a method for preparing a transparent conductive base layer to overcome the defects of the existing technology and meet the needs of practical applications. Summary of the invention
[0007] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a method for preparing a transparent conductive base layer and an electrochromic component. In the present invention, by limiting the preparation method and parameters of the transparent conductive base layer, it is possible to ensure that the square resistance will not increase, or even decrease to a lower level without changing the thickness of the transparent conductive film. Compared with fluorine-doped tin oxide materials, it has better transmittance and roughness, and compared with transparent conductive films of traditional processes, it has more stable and lower square resistance, greatly improving product performance.
[0008] To achieve this object, the present invention adopts the following technical solutions:
[0009] In a first aspect, the present invention provides a method for preparing a transparent conductive substrate, the method comprising:
[0010] After at least one layer of transparent conductive film is deposited on one side surface of the substrate by physical vapor deposition, vacuum baking treatment is performed to obtain the transparent conductive base layer; the temperature of the physical vapor deposition is ≤120°C, and the temperature of the vacuum baking treatment is 200°C to 400°C.
[0011] In the present invention, by limiting the preparation method and parameters of the transparent conductive base layer, it is possible to ensure that the square resistance will not increase, or even decrease to a lower level, without changing the thickness of the transparent conductive film. Compared with fluorine-doped tin oxide materials, the material has better transmittance and roughness, and compared with transparent conductive films produced by traditional processes, the material has more stable and lower square resistance, thereby greatly improving product performance.
[0012] It should be noted that the temperature of physical vapor deposition in the present invention is ≤120°C, and may be, for example, 20°C, 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 119°C, etc., but is not limited to the listed values, and other values not listed within the numerical range are equally applicable; the temperature of vacuum baking treatment is 200°C-400°C, and may be, for example, 200°C, 220°C, 240°C, 260°C, 300°C, 320°C, 340°C, 360°C, 380°C, 400°C, etc., but is not limited to the listed values, and other values not listed within the numerical range are equally applicable.
[0013] The temperature of physical vapor deposition in the present invention is ≤120°C because within this range, ITO will not produce microcrystalline state. 60°C to 120°C is further selected (ITO in the present invention refers to transparent conductive film) because the range of ITO Power can be better relaxed; if it is not within this range, the square resistance effect of ITO after vacuum annealing may be unsatisfactory, because the crystal microstructure of ITO has changed.
[0014] The temperature of the vacuum baking treatment of the present invention is 200°C to 400°C because the ITO square resistance can be reduced within this range, and 260°C to 380°C is further selected because it can ensure that the equipment heating and cooling time will not be too long, which is also a protection for the life of the equipment; if it is not within this range, it may cause breakage or the ITO square resistance cannot be reduced, because the annealing effect cannot be achieved when the temperature is too low, and the glass stress will break when the temperature is too high.
[0015] As a preferred technical solution of the present invention, the temperature of the physical vapor deposition is 60°C to 120°C, for example, it can be 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0016] As a preferred technical solution of the present invention, the oxygen content of the physical vapor deposition is less than 1.5%, for example, it can be 1.48%, 1.4%, 1.3%, 1.2%, 1%, 0.9%, 0.8%, 0.6%, 0.5%, 0.3%, 0.2%, 0%, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0017] The oxygen content of the physical vapor deposition of the present invention is less than 1.5% because within this range, ITO can have better oxygen vacancies. If it is not within this range, it may cause an imbalance in the ratio of holes to electrons and an unsatisfactory reduction in square resistance. This is because ITO is an n-type semiconductor that mainly relies on holes and electrons for conduction.
[0018] As a preferred technical solution of the present invention, the thickness of the transparent conductive film is 120nm to 800nm, for example, it can be 120nm, 150nm, 200nm, 300nm, 400nm, 500nm, 600nm, 700nm, 800nm, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0019] The thickness of the transparent conductive film of the present invention is 120nm to 800nm because within this range, the electrochromic product can have a better rapid color change function. If it is not within this range, it may cause slow color change or no color change. This is because the external voltage applied by the electrochromic is low, and when the square resistance is large, the current is small and the color change cannot be achieved.
[0020] As a preferred technical solution of the present invention, the temperature of the vacuum baking treatment is 230°C to 300°C, for example, it can be 230°C, 240°C, 250°C, 260°C, 270°C, 280°C, 290°C, 300°C, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0021] As a preferred technical solution of the present invention, the pressure of the vacuum baking treatment is 0.0001Pa~2000Pa, for example, it can be 0.0001Pa, 0.1Pa, 1Pa, 10Pa, 100Pa, 1000Pa, 1200Pa, 1400Pa, 1600Pa, 1800Pa, 2000Pa, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0022] As a preferred technical solution of the present invention, the pressure of the vacuum baking treatment is 0.0001Pa~0.001Pa, for example, it can be 0.0001Pa, 0.0003Pa, Pa, 0.0006Pa, 0.0009Pa, 0.001Pa, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0023] The pressure of the vacuum baking treatment of the present invention is 0.0001Pa~2000Pa, because the ITO square resistance can be reduced within this range, and 0.0001Pa~0.001Pa is further selected because less impurities can obtain a more single and dense ITO film layer; if it is not within this range, it may cause the ITO square resistance to decrease less and the film purity to be poor, because the impurities will react with the ITO film to change the film quality.
[0024] As a preferred technical solution of the present invention, the time for the vacuum baking treatment is 10 min to 120 min, for example, it can be 10 min, 20 min, 40 min, 60 min, 80 min, 100 min, 110 min, 120 min, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0025] As a preferred technical solution of the present invention, the time for the vacuum baking treatment is 30 min to 90 min, for example, it can be 30 min, 35 min, 40 min, 45 min, 50 min, 55 min, 60 min, 65 min, 70 min, 75 min, 80 min, 85 min, 90 min, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0026] The vacuum baking treatment time of the present invention is 10min to 120min, because the ITO square resistance can be reduced within this range, and 30min to 90min is further selected, because the ITO square resistance can be greatly reduced and remain stable; if it is not within this range, the ITO square resistance may not be reduced enough to achieve the desired effect, because it takes time for the ITO film to crystallize, and insufficient time will lead to insufficient crystallization.
[0027] In a second aspect, the present invention provides an electrochromic component, which includes a transparent conductive base layer prepared by the preparation method described in the first aspect, and an electrochromic layer stacked on one side of the surface of the transparent conductive base layer provided with the transparent conductive film.
[0028] It should be noted that, in the present invention, an electrochromic layer is stacked on the prepared transparent conductive base layer, wherein the electrochromic layer can be disposed on the transparent conductive base layer by sputtering, the sputtering temperature can be 280-400°C, and the time can be 5-60 minutes; so that the square resistance of the transparent conductive base layer after the subsequent high-temperature aerobic process will not only not increase but will decrease to a certain extent, thereby ensuring that the impedance of the conductive layer below the electrochromic layer is lower, and better color change efficiency can be achieved at a lower voltage.
[0029] It should be noted that the electrochromic layer in the present invention can be a single layer or multiple layers, and there is no specific limitation on its material. It can be a tungsten oxide layer, a lithium layer, a nickel layer, etc. Those skilled in the art can make adaptive adjustments according to actual conditions.
[0030] The numerical range described in the present invention not only includes the point values listed above, but also includes any point values between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0031] Compared with the prior art, the present invention has the following beneficial effects:
[0032] In the present invention, by limiting the preparation method and parameters of the transparent conductive base layer, it is possible to ensure that the square resistance will not increase, or even decrease to a lower level, without changing the thickness of the transparent conductive film. Compared with fluorine-doped tin oxide materials, the material has better transmittance and roughness, and compared with transparent conductive films produced by traditional processes, the material has more stable and lower square resistance, thereby greatly improving product performance. DETAILED DESCRIPTION
[0033] The technical solution of the present invention is further illustrated below through specific implementation methods.
[0034] Example 1
[0035] This embodiment provides a method for preparing a transparent conductive base layer, which includes:
[0036] A transparent conductive film is deposited on one side of the substrate by physical vapor deposition, and then vacuum baking is performed to obtain a transparent conductive base layer; the temperature of the physical vapor deposition is 110°C, and the temperature of the vacuum baking is 230°C.
[0037] The oxygen content of the physical vapor deposition is 0.8%, the thickness of the transparent conductive film is 700 nm, the pressure of the vacuum baking treatment is 0.0001 Pa, and the time of the vacuum baking treatment is 40 min.
[0038] Example 2
[0039] This embodiment provides a method for preparing a transparent conductive base layer, which includes:
[0040] A transparent conductive film is deposited on one side of the substrate by physical vapor deposition, and then vacuum baking is performed to obtain a transparent conductive base layer; the temperature of the physical vapor deposition is 110°C, and the temperature of the vacuum baking is 270°C.
[0041] The oxygen content of the physical vapor deposition is 0.8%, the thickness of the transparent conductive film is 700 nm, the pressure of the vacuum baking treatment is 0.0001 Pa, and the time of the vacuum baking treatment is 40 min.
[0042] Example 3
[0043] This embodiment provides a method for preparing a transparent conductive base layer, which includes:
[0044] A transparent conductive film is deposited on one side of the substrate by physical vapor deposition, and then vacuum baking is performed to obtain a transparent conductive base layer; the temperature of the physical vapor deposition is 110°C, and the temperature of the vacuum baking is 230°C.
[0045] The oxygen content of the physical vapor deposition is 0.8%, the thickness of the transparent conductive film is 700 nm, the pressure of the vacuum baking treatment is 0.0001 Pa, and the time of the vacuum baking treatment is 15 min.
[0046] Example 4
[0047] This embodiment provides a method for preparing a transparent conductive base layer, which includes:
[0048] A transparent conductive film is deposited on one side of the substrate by physical vapor deposition, and then vacuum baking is performed to obtain a transparent conductive base layer; the temperature of the physical vapor deposition is 110°C, and the temperature of the vacuum baking is 270°C.
[0049] The oxygen content of the physical vapor deposition is 0.8%, the thickness of the transparent conductive film is 700 nm, the pressure of the vacuum baking treatment is 0.0001 Pa, and the time of the vacuum baking treatment is 15 min.
[0050] Example 5
[0051] This embodiment provides a method for preparing a transparent conductive base layer, which includes:
[0052] A transparent conductive film is deposited on one side of the substrate by physical vapor deposition, and then vacuum baking is performed to obtain a transparent conductive base layer; the temperature of the physical vapor deposition is 110°C, and the temperature of the vacuum baking is 270°C.
[0053] The oxygen content of the physical vapor deposition is 1.6%, the thickness of the transparent conductive film is 700 nm, the pressure of the vacuum baking treatment is 0.0001 Pa, and the time of the vacuum baking treatment is 40 min.
[0054] Comparative Example 1
[0055] This comparative example provides a method for preparing a transparent conductive base layer, which is different from Example 1 in that the temperature of the vacuum baking treatment is 160° C., and the other parameters and test conditions are the same as those of Example 1.
[0056] Comparative Example 2
[0057] This comparative example provides a method for preparing a transparent conductive base layer, which is different from Example 1 in that the pressure of the vacuum baking treatment is 5000 Pa, and the other parameters and test conditions are the same as those in Example 1.
[0058] Comparative Example 3
[0059] This comparative example provides a method for preparing a transparent conductive base layer, which is different from Example 1 in that no vacuum baking treatment is performed.
[0060] The transparent conductive substrate prepared above was subjected to variable tests such as different baking temperatures, oxygen contents, and baking pressures, and then the square resistance values were measured and compared using a four-probe instrument; the results are shown in Table 1 below.
[0061] Table 1 Test results in embodiments and comparative examples
[0062]
[0063]
[0064] From Table 1 above, we know that:
[0065] The present invention limits the preparation method and parameters of the transparent conductive base layer, and can ensure that the square resistance does not increase, or even decreases to a lower level without changing the thickness of the transparent conductive film. Compared with fluorine-doped tin oxide materials, the present invention has better transmittance and roughness, and compared with transparent conductive films of traditional processes, it has more stable and lower square resistance, greatly improving product performance.
[0066] The specific embodiments described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
[0067] The present invention illustrates the detailed method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed method, that is, it does not mean that the present invention must rely on the above-mentioned detailed method to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing a transparent conductive base layer, characterized in that: The preparation method comprises: A surface of one side of the substrate is subjected to a vacuum baking treatment after at least one layer of transparent conductive film is physically vapor deposited to obtain the transparent conductive base layer; The temperature of the physical vapor deposition is ≤120°C, and the temperature of the vacuum baking treatment is 200°C to 400°C.
2. The preparation method according to claim 1, characterized in that: The temperature of the physical vapor deposition is 60°C to 120°C.
3. The preparation method according to claim 1 or 2, characterized in that: The oxygen content of the physical vapor deposition is <1.5%.
4. The preparation method according to any one of claims 1 to 3, characterized in that: The thickness of the transparent conductive film is 120nm-800nm.
5. The preparation method according to any one of claims 1 to 4, characterized in that: The temperature of the vacuum baking treatment is 230°C to 300°C.
6. The preparation method according to any one of claims 1 to 5, characterized in that: The pressure of the vacuum baking treatment is 0.0001Pa to 2000Pa.
7. The preparation method according to claim 6, characterized in that: The pressure of the vacuum baking treatment is 0.0001Pa to 0.001Pa.
8. The preparation method according to any one of claims 1 to 7, characterized in that: The vacuum baking treatment lasts for 10 to 120 minutes.
9. The preparation method according to claim 8, characterized in that: The vacuum baking treatment takes 30 to 90 minutes.
10. An electrochromic component, characterized in that: The electrochromic component comprises a transparent conductive base layer prepared by the preparation method according to any one of claims 1 to 9, and an electrochromic layer stacked on a surface of one side of the transparent conductive base layer on which the transparent conductive film is provided.
Citation Information
Patent Citations
All-solid state electrochromic device preparation method and prepared electrochromic glass
CN104898344A
Inorganic electrochromic charge storage electrode and preparation method thereof
CN107315299A